Sport specialization in Swedish football players: Investigating a model of antecedents and outcomes - Söderström, T.; Garn, A. C. (European Journal of Sport Science, 2023)
Drawing on data from the present and former football players (N = 1026) selected to a national football talent programme at the age of 15, this study explores a model of sport specialisation. We examined three specific aspects of sport specialisation including early football specialisation, participation in youth elite football training environments (i.e. academies) and enrolment in upper secondary football specialisation schools. Antecedents of these sport specialisation factors included gender (i.e. sociocultural), grit (i.e. personality) and perceptions of family finances (i.e. social). Outcomes focused on adult football participation at the age of 21 including elite skill acquisition (i.e. playing elite football) and personal development (i.e. participation in non-elite football). Findings revealed that females were less likely to gain access to elite football training or school specialisation environments. There was also a positive association between grit and participation in elite training environments. In terms of outcomes, players, who got trained in elite training environments during adolescence, were twice as likely to play elite football at the age of 21, while those who attended football specialisation schools were more likely to participate in non-elite football at the age of 21. Early specialisation was not associated with either adult participation outcome. This is one of the few studies to date addressing diverse antecedents and outcomes of sport specialisation factors. Understanding how sport specialisation practices relate to future skill acquisition and personal development can provide guidance for maximising the benefits of youth sport programming.